Effects of erythropoietin on emotional processing biases in patients with major depression: an exploratory fMRI study. - Miskowiak, K; Favaron, E; Hafizi, S; Inkster, B; Goodwin, G; Cowen, P; Harmer, C (2009)
INTRODUCTION: Erythropoietin (Epo) has neurotrophic effects and may be a novel therapeutic agent in the treatment of depression. We have found antidepressant-like effects of Epo on emotional processing and mood in healthy volunteers. OBJECTIVE: The current study aimed to explore the effects of Epo on the neural processing of emotional information in depressed patients. MATERIALS AND METHODS: Seventeen patients with acute major depressive disorder were randomised to receive Epo (40,000 IU) or saline iv in a double-blind, parallel-group design. On day 3, we assessed neural responses to positive, negative and neutral pictures during fMRI followed by picture recall after the scan. Mood and blood parameters were assessed at baseline and on day 3. RESULTS: Epo reduced neural response to negative vs. positive pictures 3 days post-administration in a network of areas including the hippocampus, ventromedial prefrontal and parietal cortex. After the scan, Epo-treated patients showed improved memory compared with those that were given placebo. The effects occurred in the absence of changes in mood or haematological parameters, suggesting that they originated from direct neurobiological actions of Epo. CONCLUSIONS: These findings are similar to the effects of conventional antidepressants and opposite to the negative biases in depression. The central effects of Epo therefore deserve further investigation as a potential antidepressant mechanism.